Rotational Periods of Asteroids 2167 Erin and 1084 Tamariwa. - Lorenzen, Kayla; Ulrich, Sarah A. (My University, 2009)
We observed and analyzed asteroids 2167 Erin and 1084 Tamariwa to find their light curves and their rotational periods.
Color poster with text and images describing research conducted by Kayla Lorenzen and Sarah Ulrich, advised by Lyle Ford and George Stecher.
Keywords: Asteroids--Photographic measurements; 2167 Erin (Asteroid); 1084 Tamariwa (Asteroid); Posters